2019
DOI: 10.1177/2325967119864088
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Fast, Safe, and Effective All-Inside Arthroscopic Rotator Cuff Repair Technique: Results of 1000 Consecutive Cases

Abstract: Background: Arthroscopic rotator cuff repair is a common but technically difficult surgical technique. This study describes a novel arthroscopic rotator cuff repair technique where the repair was performed while visualized entirely from the glenohumeral joint. A single-row knotless tension band inverted mattress suture technique was utilized with fixation obtained via suture anchors. The technique was relatively easy to perform and demonstrated good repair strength and footprint compression in an ex vivo ovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Our group previously investigated factors that were predictive of a rotator cuff retear in a cohort of 1000 patients. 12 We found that operative time was a significant independent predictor of rotator cuff retears at 6 months postoperatively. Other factors that were identified to be significant independent predictors of a retear were anteroposterior tear length, mediolateral tear length, tear thickness, and patient age at surgery.…”
Section: Re-tear Ratementioning
confidence: 61%
See 1 more Smart Citation
“…Our group previously investigated factors that were predictive of a rotator cuff retear in a cohort of 1000 patients. 12 We found that operative time was a significant independent predictor of rotator cuff retears at 6 months postoperatively. Other factors that were identified to be significant independent predictors of a retear were anteroposterior tear length, mediolateral tear length, tear thickness, and patient age at surgery.…”
Section: Re-tear Ratementioning
confidence: 61%
“…51 Detailed outcomes of this approach alone are presented elsewhere. 12 In cases where undersurface repair was unable to be completed, the tendon was approached from the side of the subacromial bursa, and a bursal-sided repair technique was utilized. 31 Before repair, partial-thickness tears were converted to full-thickness tears.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The arthroscopic treatment of chronic, massive rotator cuff tears can be technically demanding, with longer operative times, higher costs, and possible increased rerupture rates compared with open treatment [ 8 , 17 ]. Therefore, open and mini-open procedures are still common and frequently used in rotator cuff repair [ 8 ]. Both the SLKS and DLKS are applicable to arthroscopic technique, but less technically demanding in open repair.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic repair techniques have become popular in recent years, with possible advantages in visualization of tears and additional intra-articular lesions, less scar formation, and shorter postoperative recovery [ 4 ]. On the other hand, arthroscopic repair can be technically demanding and time-consuming in comparison with mini-open procedures [ 8 ]. The modified Mason-Allen stitch (mMAS) technique is common in mini-open procedures and considered to be superior to the simple or mattress stitch with respect to initial fixation strength [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who had (1) irreparable rotator cuff tears, (2) partially repaired rotator cuff tears, (3) rotator cuff tears repaired using interposition grafts or onlay biological patches, (4) isolated subscapularis repairs, (5) rotator cuff repairs associated with calcific tendinitis, or (6) associated fractures or (7) who had undergone concurrent stabilization procedures were excluded. Patients who underwent another operation not related to their index surgery (eg, rotator cuff repair on the other side within 6 months of the index surgery) that would have delayed return to work were also excluded.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%